Developmental and legal aspects of general insurance in the Caribbean with special reference to the OECS countries - Denbow, Claude H. (UN. ECLAC Port of SpainTT, 1987)
Looks at the development of insurance legislation; structure of existing markets; concept of the regional insurance company; techniques of governmental supervision of general insurance companies; legal implications of the operation of insurance intermediaries; consequences of the insolvency of a general insurer; and the adequacy of compulsory insurance.